The Impact of D-Dimer on Postoperative Deep Vein Thrombosis in Patients with Thoracolumbar Fracture Caused by High-Energy Injuries - Wang, Haiying; Lv, Bing; Li, Weifeng; Wang, Shunyi (Clinical and applied thrombosis/hemostasis, 2022)
Objective To investigate the dynamic variation of D-dimer and to evaluate the efficacy and accuracy of D-dimer level in patients with thoracolumbar fractures caused by high-energy injuries. Methods A total of 121 patients with thoracolumbar fractures caused by high-energy injuries were retrospectively identified and included in this study. There were 83 males and 38 females, with an average age of 48.6 ± 11.2 years. All patients were treated with either screw fixation surgery or decompression fixation surgery. The D-dimer levels were measured 1 day before surgery and on the first, third, and fifth days after surgery. The dynamic variation of D-dimer and the effects of risk factors on D-dimer levels were analysed. A receiver operating characteristic (ROC) curve analysis was performed and the appropriate D-dimer cut-off level was determined for deep vein thrombosis (DVT) screening. Results Due to a trough on the third day, D-dimer levels grew in an unsustainable manner following surgery (P < 0.001). Patients with the operation time >120 min (P = 0.009) and those with an American Spinal Injury Association (ASIA) score A-C (P < 0.001) had higher D-dimer levels. The area under the curve of D-dimer was the greatest on the third day. Applying stratified cut-off values did not change the sensitivity, specificity and negative predictive value in the group with an operation time >120 min, and ASIA score A-C group. Conclusions D-dimer levels elevated with fluctuation in patients with thoracolumbar fractures caused by high-energy injuries after surgery. Both operation time and ASIA score had an impact on D-dimer levels. Regarding DVT diagnoses, the diagnostic value of D-dimer was highest on the third day postoperatively, and stratified cut-off values by these two factors did not show better diagnostic efficacy compared with a collective one.